Diversidad de escarabajos coprófagos (Coleoptera: Scarabaeinae) en un remanente ribereño y un fragmento de bosque húmedo tropical en Córdoba, Colombia (2016)
The expansion of the agricultural frontier produces fragmented landscapes, habitat decline and loss of diversity. In these landscapes, remnants of riparian vegetation are important elements to maintain biodiversity.